Public Companies’ Cash and Accrual Rates of Return in Selected European Countries During the Coronavirus Pandemic - Tomasz MAŚLANKA (Communications of International Proceedings, 2021)
The paper presents the issue of profitability of public listed companies from selected European countries during the coronavirus pandemic relative to their profitability in previous years. The analysis focuses on financial data disclosed by entities listed on the stock exchanges in Poland, Germany, France, Great Britain and Spain. A comparison is made between the cash and accrual rates of return on their activities in 2016-2020, i.e., for the four successive years before to the pandemic versus 2020, i.e., the year in which the Covid-19 pandemic determined the functioning of numerous areas of business activity. The theoretical part of the paper presents considerations related to the construction of analytical indicators based on the profit and loss account and the cash flow statement.
Keywords: Cash Flow Statement; Accrual Rate of Return; Cash Rate of Return; Coronavirus Pandemic